2013
DOI: 10.1038/bjc.2013.283
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies different sub-types of retinoblastoma

Abstract: Background:Mutation of the RB1 gene is necessary but not sufficient for the development of retinoblastoma. The nature of events occurring subsequent to RB1 mutation is unclear, as is the retinal cell-of-origin of this tumour.Methods:Gene expression profiling of 21 retinoblastomas was carried out to identify genetic events that contribute to tumorigenesis and to obtain information about tumour histogenesis.Results:Expression analysis showed a clear separation of retinoblastomas into two groups. Group 1 retinobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 56 publications
11
70
0
Order By: Relevance
“…52 Gene expression profiles were initially proposed to reveal only a single relatively homogeneous class of retinoblastoma 55 and were subsequently proposed to segregate RB1 −/− retinoblastomas into two subtypes. 56 However, analyses of a larger cohort recently revealed a spectrum of phenotypes reflecting progression from a state with high photoreceptor differentiation and few cytogenetic changes to a state with lower differentiation, increased mRNA and ribosome biogenesis and mitosis gene expression signatures, and increased cytogenetic aberrations. 54 Thus, RB1 −/− retinoblastomas appear to progress from self-limiting retinomas to differentiated retinoblastoma to less differentiated malignancies.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…52 Gene expression profiles were initially proposed to reveal only a single relatively homogeneous class of retinoblastoma 55 and were subsequently proposed to segregate RB1 −/− retinoblastomas into two subtypes. 56 However, analyses of a larger cohort recently revealed a spectrum of phenotypes reflecting progression from a state with high photoreceptor differentiation and few cytogenetic changes to a state with lower differentiation, increased mRNA and ribosome biogenesis and mitosis gene expression signatures, and increased cytogenetic aberrations. 54 Thus, RB1 −/− retinoblastomas appear to progress from self-limiting retinomas to differentiated retinoblastoma to less differentiated malignancies.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…85-88 Gene expression profiling (GEP) of mRNA and comparative genomic hybridization (CGH) of DNA were utilized recently to evaluate 21 retinoblastomas. 89 Results of this initial study showed different patterns of retinal gene expression that when analyzed by unsupervised hierarchical clustering, followed by principle component analysis to categorize the retinoblastomas into three groups. 89 Group 1 retinoblastomas expressed genes found in early retinal development, thus suggesting a RPC origin.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Analysis of gene expression profiles in Rb patients has revealed that there are two types of Rb, each with a specific cell of origin. Unlike the second type, the first type exhibits an invasive growth pattern [89]. Spread of tumor cells from the primary site to distant organs requires the acquisition of specific features such as invasion, intravasation, survival in the circulation, extravasation and, finally, colonization within the target organ.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%